"A Agathotopia de Charles Sanders Peirce" - Dib, Maria Augusta Nogueira Machado (2008)
If not through the means of psychological subjective belief, nor through the path of religious belief, how can a philosophical, logical and objective belief attribute to love the role of law under which continuous evolutionary development of life occurs? Unacquainted with the ideological categorical imperatives such as moral, philosophical, and psychological order (i.e. Kantian) or the religious orders (such as Christian), Peirce s pragmaticist belief in the universal instinctive action to live, extends this instinct to a propensity for the non-individual growth and development toward the summum bonum from micro to macroscopic organism, through mankind itself: «progress comes from every individual who grounds his individuality on the affection towards his neighbors» (CP 6.294). Peirce s philosophical architecture which is both objective and logical postulates love - agape as a condition of evolutionary cosmic law, where the cosmos is mind and endowed with life (CP 6.289). According to Nicola Abbagnano s Dictionary of Philosophy, page 27, Agapism is a term adopted by Peirce to designate the "law of evolutionary love", since the cosmic evolution tend to boost brotherly love among mankind. The same Dictionary defines Agathology to mean the doctrine of Good as part of Ethics. If the pragmatist William James, a contemporary and friend of Peirce, had held onto the belief of action as the ultimate purpose, then there would be a possibility of ethical action as an ultimate purpose for him. Charles Sanders Peirce differs from him, preferring to be considered a pragmaticist (CP 5.414) and focusing on the research of the evolutionary process which leads to the summum bonum, where Aesthetics, Ethics and Logics converge into the same purpose, the Wellness (EP 2.27). The Agathotopia, term used by James E. Meade, Nobel Prize award in Economics (1977), appears in the universe of the political economy as an alternative model (a combination of the best in the capitalist system with the best in the socialist system). It would possibly be a model for the construction of a good society to live in, such as an ideal place depicted by Thomas Moore s Utopia (1516) and other utopias throughout philosophical thought since the Republic of Plato . According to Peirce, the so-called - Agathotopia - different and original, will not be reduced to a specific and ideal geographical place to live as sought by the utopias, and even less a post-death base as the religions postulate. It would be neither a socio-political nor an economic model to promote the collective welfare in the reality of the existential universe. Charles Sanders Peirce s Agathotopia has been proposed in all his scientific metaphysical architecture, in his realistic philosophy and logic of his objective idealism, in his Synechism. It develops into the ongoing semioses between sign-object-interpretant, and the evolving process of reasonability, a continuous teleological self-corrective movement toward the evolutionary enhancement. It gives credit to agapic love, the function of mental law as a creative and supportive habit of the universe in this evolutionary process. If Peirce believes in that dynamic mental loving action that tends to the Admirable, Fair and True Purpose then he might not be proposing just one more utopia in the history of Philosophy, but Agathotopia for the first time. An tópos to the Summum Bonum